2017
DOI: 10.1016/j.neuropsychologia.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Pre-stimulus alpha oscillations over somatosensory cortex predict tactile misperceptions

Abstract: Cite this article as: Matt Craddock, Ellen Poliakoff, Wael El-deredy, Ekaterini Klepousniotou and Donna M. Lloyd, Pre-stimulus alpha oscillations over somatosensory cortex predict tactile misperceptions, Neuropsychologia, http://dx.doi.org/10. 1016/j.neuropsychologia.2016.12.030 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 48 publications
(89 reference statements)
14
63
0
Order By: Relevance
“…49 The baseline high-frequency alpha power predicted a tactile misperception of the somatosensory system. 50 In the present study, the high-frequency alpha rhythm represented a sensory blocking or modulation, and the decrease of brain activity was associated with elevated alpha rhythms. A negative correlation between alpha power and glucose metabolic rates has previously been reported in healthy participants.…”
Section: Discussionsupporting
confidence: 44%
“…49 The baseline high-frequency alpha power predicted a tactile misperception of the somatosensory system. 50 In the present study, the high-frequency alpha rhythm represented a sensory blocking or modulation, and the decrease of brain activity was associated with elevated alpha rhythms. A negative correlation between alpha power and glucose metabolic rates has previously been reported in healthy participants.…”
Section: Discussionsupporting
confidence: 44%
“…Beta-band power in particular is associated with feedback signals (Bastos et al, 2015), stronger attention and top-down control (Buschman and Miller, 2007;Salazar et al, 2012), and the prioritization of the current brain states over new inputs (Spitzer and Haegens, 2017). In support to this view, stronger low frequency (<30 Hz) oscillations attenuate early evoked sensory responses (Iemi et al, 2019), increase the criterion of perceptual detection (resulting in fewer detections) by modulating baseline excitability (Limbach and Corballis, 2016;Benwell et al, 2017;Craddock et al, 2017;Iemi et al, 2017) and degrade performance in perceptual decisions (Haegens et al, 2011).…”
Section: Discussion (1500)mentioning
confidence: 97%
“…In line with such a neural underpinning, a series of studies suggested that reduced alpha power correlates with enhanced perceptual sensitivity (Ergenoglu, et al, 2004;Hanslmayr, et al, 2007;van Dijk, Schoffelen, Oostenveld, & Jensen, 2008;Mathewson, Gratton, Fabiani, Beck, & Ro, 2009;Busch, Dubois, & VanRullen, 2009;Obleser & Weisz, 2012). Yet, recent studies suggested a different picture whereby the alpha power does not modulate perceptual sensitivity or accuracy per se but rather reflects a bias in perceptual decision making (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Samaha, Iemi, & Postle, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Wöstmann, Waschke, & Obleser, 2018). While the precise role of alpha in a mechanistic cascade of sensory-decision processes remains debated, we here consider alpha oscillations from a new perspective, through the prism of idiosyncratic and temporary biases.…”
Section: A Mechanistic Role Of Alpha Powermentioning
confidence: 98%
“…One neural signature involved in this process supposedly is alpha band activity (van Kerkoerle, et al, 2014;Michalareas, et al, 2016;Sherman, Kanai, Seth, & VanRullen, 2016;Mayer, Schwiedrzik, Wibral, Singer, & Melloni, 2016), generally known to shape the perception of forthcoming stimuli (Ergenoglu, et al, 2004;Hanslmayr, et al, 2007;van Dijk, Schoffelen, Oostenveld, & Jensen, 2008;Mathewson, Gratton, Fabiani, Beck, & Ro, 2009). Recent studies have suggested that pre-stimulus alpha activity may reflect the criterion used to commit a specific response and may hence reflect a perceptual or decisional bias (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Rohe, Ehlis, & Noppeney, 2019). Along such a role in perceptual decision making, alpha activity was shown to correlate with subjective awareness (Benwell, et al, 2017;Lange, Oostenveld, & Fries, 2013;Gulbinaite, İlhan, & VanRullen, 2017) and decision confidence (Samaha, Iemi, & Postle, 2017;Wöstmann, Waschke, & Obleser, 2018).…”
Section: Introductionmentioning
confidence: 99%